ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PENUMPANG KERETA API PRAMEKS DI STASIUN KLATEN - Tri Widodo; Andung Jati Nugroho (Jurnal Disprotek, 2019)
Abstract PT Kereta Api Indonesia provides services to prospective passengers in the provision of services related to the only railway services in Indonesia. In this study aims to determine the extent of the quality of service that has been given by Klaten Station to train passengers. This research was carried out on trainers. The study was conducted by distributing 25 questionnaires to train passengers at Klaten Station. Then tested the validity and reliability, to determine the suitability of the distributed questionnaire, then measured the level of importance with Service Performance, then carried out the calculation of the Customer Satisfaction Index to determine the level of passenger satisfaction, then make a chart Importance Performance Analysis to determine the level of importance and customer satisfaction. The calculation results from Service Performance obtained the value of the suitability level of 44.45% -77.45%, the value of the Customer Satisfaction Index of 61.60% which is included in the Very Poor's criteria or needs to be improved, the Importance Performance Analysis calculation has the highest priority quality attributes namely the attributes number 6, 7, 12, 20, and 21. With the proposed improvements using the Theory Resheniya Izobreatatelskikh Zadatch, that is, increase the number of seats for prospective passengers and introductory. Adding supporting facilities that do not yet exist in the Klaten Station environment, PT KAI will educate Klaten Station officers to be more disciplined and prioritize the best service to customers. Keywords: Servqual, Customer Satisfaction, Performance, Importance